KEPRIBADIAN TERHADAP GAYA KELEKATAN DALAM HUBUNGAN PERSAHABATAN - Susanti Prasetyaningrum; Finda Oktaviani Rahma (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
The purpose of this study was to determine the influence of the Big Five Personality dimensions to the attachment style on adolescent friendship-relation. There were 220 subjects taken with simple random sampling technique from MAN 2 Tulungagung. The data were analyzed by multiple linear regression. The results found that there was a correlation between the Big Five Personality dimensions and attachment style. The Big Five Personality dimensions has effected on attachment style as well. Extroversion dimension is positively correlated and able to predict secure attachment style with (R=0.297). Openness dimension is negatively correlated and able to predict Fearful attachment style with (R=-0.373). Conscientiousness is positively correlated and able to predict Dismissing attachment style with (R=0.344). However, the dimensions of the Big Five Personality were not significant enough to predict preoccupied attachment style.